Michael J. Ruggerio, The evolution of the go-between in Spanish literature through the sixteenth century. University of California Press, Berkeley and Los Angeles, 1966; 102 pp. (UCPMPh, 78). - Kersten, Raquel (Nueva Revista de Filología Hispánica (NRFH), 1972)
Se reseñó el libro: The evolution of the go-between in Spanish literature through the sixteenth century.